2021
DOI: 10.1080/21655979.2021.1980671
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of microalgal biofilm: a review on prediction of adhesion on substrates

Abstract: In view of high energy cost and water consumption in microalgae cultivation, microalgal-biofilmbased cultivation system has been advocated as a solution toward a more sustainable and resource friendlier system for microalgal biomass production. Algal-derived extracellular polymeric substances (EPS) form cohesive network to interconnect the cells and substrates; however, their interactions within the biofilm are poorly understood. This scenario impedes the biofilm process development toward resource recovery. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 114 publications
0
22
0
Order By: Relevance
“…Moreover, higher agitation speed induced weaker extrapolymeric substances (EPS) bonding between the algal cells, making the cells to have poor resistance to high hydrodynamic stress and ended up in damaged cells 21 . Biomass growth was optimal at intermediate agitation speeds, resulting in increased EPS secretion that act as a bioglue to build a firm biofilm around the cells, which was beneficial in capturing nutrients for cells from culture medium 22,23 . During cell division stage, cells were more sensitive toward the shear stress induced by high agitation speeds as speculated by other studies 24 .…”
Section: Resultsmentioning
confidence: 89%
“…Moreover, higher agitation speed induced weaker extrapolymeric substances (EPS) bonding between the algal cells, making the cells to have poor resistance to high hydrodynamic stress and ended up in damaged cells 21 . Biomass growth was optimal at intermediate agitation speeds, resulting in increased EPS secretion that act as a bioglue to build a firm biofilm around the cells, which was beneficial in capturing nutrients for cells from culture medium 22,23 . During cell division stage, cells were more sensitive toward the shear stress induced by high agitation speeds as speculated by other studies 24 .…”
Section: Resultsmentioning
confidence: 89%
“…The nature of the cell wall of microalgae differs among the species, further, it has been shown that not only the exposure conditions of the culture media may affect the physiology of the microalgae leading to the production of extracellular polymeric substances (EPS) (Cheah & Chan, 2021), but also the nutrient composition may alter the biochemical response (Sánchez-Bayo et al, 2020). Moreover, it has also been reported that the composition of the cell wall of N. oleoabundans can be altered when the microalgae is cultivated under different growing conditions (Rashidi et al, 2019), making it more resistant when cultivated in marine water under nitrogen deprivation (Safi et al, 2020) .It was important to evaluate the effect of pretreatment under different culture conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Artificial light was spread equally over all flumes and light density averaged 9.5 µmol m -2 s -1 and was the maximum even light density achievable with the provided light sources. We used a light cycle of 12:12 and 18:6 (Cheah and Chan 2021) hours of light versus dark early and later in the experiment to mimic natural light cycles at first and then to encourage biofilm growth later in the experiment. Each flume was equipped with microscope slides (6) and clay tiles (8) to quantify biofilm growth.…”
Section: Methodsmentioning
confidence: 99%